Design and Testing of a Wing with a Morphing Trailing Edge - Pinho, João (2023)
In recent years, the interest in morphing technologies has been continuously growing. Many designs have been developed, but some are very complex to manufacture. The main goal of this paper is to present a wing design with a morphing trailing edge that is easy to manufacture and control while allowing the execution of appropriate aerodynamic studies in wind tunnel. Using computer-aided design and 3D printing, a wing that is easily controlled with easy-to-use hardware is developed, manufactured, and studied using flow visualization and force acquisition. Flow visualization showed that the presence of curvature delays stall occurrence when compared to the symmetrical configuration, where flow separation starts right at the leading edge. This is validated by force measurements where curvature plays an important role regarding lift enhancement. This design will allow for a wider range of studies, including unsteady conditions, which can offer insights concerning aerodynamic surfaces design.